Effects of fungicides and biofungicides on Rhizoctonia solani, a pathogen of pepper - Mihajlović, Milica; Rekanović, Emil; Hrustić, Jovana; Grahovac, Mila; Stevanović, Marija; Tanović, Brankica (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2020)
In vitro and in vivo sensitivity of Rhizoctonia solani to several commercial fungicides and biofungicides was studied. An isolate of R. solani, derived from diseased pepper plants originating from a greenhouse in Knjaževac, Serbia, was used. The highest effi cacy in R. solani control under greenhouse conditions was achieved by iprodione (95.80%, compared to control), although diff erences in the eff ectiveness of iprodione, tea tree oil, azoxystrobin and thiophanate-methyl were not statistically signifi cant. The isolate was sensitive to all tested products in vitro. The obtained EC50s were: 0.43 mg/l for iprodione, 1.84 mg/l for thiophanate-methyl, 13.84 mg/l for prochloraz, 430.37 mg/l for fluopyram, 596.60 mg/l for azoxystrobin, and 496.79 mg/l for tea tree oil.